Psychological Evidence for Assumptions of Path-Based Inheritance Reasoning - VOGEL, CARL (My University, 1994)
The psychological validity of inheritance reasoners is clarified. Elio and Pelletier (1993) presented the first pilot experiment exploring some of these issues. We investigate other foundational assumptions of inheritance reasoning with defaults: transitivity, blocking of transitivity by negative defaults, preemption in terms of structurally defined specificity and structurally defined redundancy of information. Responses were in accord with the assumption of at least limited transitivity, however, reasoning with negative information and structurally defined specificity conditions did not support the predictions of the literature. `Preemptive? links were found to provide additional information leading to indeterminacy, rather than providing completely overriding information as the literature predicts. On the other hand, results support the structural identification of certain links as redundant. Other findings suggest that inheritance proof-theory might be excessively guided by its syntax.
Proceedings of the Sixteenth Annual Conference of the Cognitive Science Society
PUBLISHED
Atlanta, Ga
Keywords: Computer Science; Ageing; Cancer; Creative Arts Practice; Creative Technologies; Digital Humanities; Inclusive Society; Intelligent Content & Communications; International Integration; Next Generation Medical Devices; Smart & Sustainable Planet; Telecommunications; Cognitive science; Computational linguistics; Formal Semantics; SEMANTICS; cognitive computing